Digitalisasi Pelaporan Indeks K menggunakan K-Smard: Studi Empiris pada Industri Kelapa Sawit Kalimantan Selatan - Dahniar, Dahniar; Sudirwo, Sudirwo; Mikrianto, Edi; Herteno, Rudy; Wibowo, Alan Dwi; Septiana, Nurmelati (Jurnal Samudra Ekonomi dan Bisnis, 2026)
The K Index, which serves as the basis for revenue sharing between palm oil mills and smallholders, still exhibits monthly fluctuations that should not theoretically occur. This condition highlights the need for a more consistent, standardized, and user-friendly K Index calculation system supported by digital applications. This study aims to develop and validate the K-SMARD application as an information system for the automated calculation and reporting of the K Index. System development employed the waterfall model, while testing used real K Index data from palm oil mills and was evaluated using a comparative statistical approach against the conventional Excel-based method. The results show that K-SMARD produces accurate and consistent K Index values with no significant differences, while improving efficiency and reporting reliability.